2006
DOI: 10.1682/jrrd.2005.05.0160
|View full text |Cite
|
Sign up to set email alerts
|

Skin and bone integrated prosthetic pylon: A pilot animal study

Abstract: Abstract-Direct skeletal attachment of limb prostheses is a viable alternative to traditional techniques that are based on a socket-residuum interface. Direct skeletal attachment may be a better or even the only method for patients with a very short residuum and high soft-tissue volume. The problem of integrating the prosthetic pylon with residual skin during direct skeletal attachment of a limb prosthesis has not been solved, and the use of a completely porous prosthetic pylon has not been the subject of focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…In the tissues surrounding the implants at the skin level and under the skin, no signs of inflammation were seen in the experimental SBIP-1 group, while some abscess indicators were seen in the control group. We concluded that the experimental SBIP-1 provided an inviting environment for the surrounding tissues [15].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In the tissues surrounding the implants at the skin level and under the skin, no signs of inflammation were seen in the experimental SBIP-1 group, while some abscess indicators were seen in the control group. We concluded that the experimental SBIP-1 provided an inviting environment for the surrounding tissues [15].…”
Section: Introductionmentioning
confidence: 80%
“…Following our preliminary in vitro [21] and in vivo [15] studies, we found that a combined pore size of 50 m and porosity of >35 percent were appropriate for skin and bone ingrowth. However, the initial samples of sintered spherical particles were not sufficiently strong to be considered for further in vivo studies.…”
Section: Manufacturing and Mechanical Testingmentioning
confidence: 88%
See 1 more Smart Citation
“…The porous composite skin and bone integrated pylon (SBIP) system was developed by Poly-Orth International (Sharon, Massachusetts) with several modifications [21]. The system was intended for a one-stage DSA procedure [22], similar to the Percutaneous Osseointegrated Prostheses system (POP) (IMDS Co-Innovative; Logan, Utah) [23], Endo-Exo Femoral Prosthesis (EEFP) (Eska Orthodynamics GmbH [formerly ESKA IMPLANTS AG]; Lubeck, Germany) [24], and the Intraosseous Transcutaneous Amputation Prosthesis (ITAP) system (Stanmore Group [University College; London, United Kingdom]) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, three systems: OPRA [29], EEEF [30], and ITAP [31], have been used in human patients. The POP [32] and SBIP [20, 24] systems are being used in continuing pre clinical and pilot animal studies, and the AEAHBM [33] and UA [34] systems are being used in pilot animal studies.…”
Section: Methodsmentioning
confidence: 99%